The Effect of Storage on The Quality of Ict Eggs - I W. G. T., Warmana; Dewi, G. A. M. K.; Wijana, I W. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
Eggs are a product that easily prevents and reduces the quality of microbial entry into eggs during storage, therefore a study of duck egg storage was carried out for 21 days. This study discusses the length of storage of the quality of duck eggs stored on the Bedugul plateau. The design used was a completely randomized design (CRD) with 4 preparations and 5 replications, and each replication consisted of 3 eggs, so that the eggs used were 60 duck eggs. The variables discussed were exterior quality and egg interior, exterior quality of eggs given egg weight and egg shape index, thick egg interior quality, eggshell, pH, egg yolk color, and (HU) Haugh Unit. The results showed significant differences (P <0.05) in the interior, namely eggshell weight, egg yolk color, and HU eggs, whereas the egg weight, egg shape index, shell thickness, pH showed no significant difference (P> 0, 05). Can be removed as a setting without 0 days storage, and at 7, 14, and 21 days storage on interior duck eggs improve quality on eggshell weight, egg yolk color, Haugh Unit (HU) and eggs at room temperature and still show AA grade values and microbial contamination is still below the Indonesian National Standard (SNI).   Keywords : Duck eggs, duck egg quality, egg storage time, plain high